Report from the Bombay Library Network - Ramani, S. (DESIDOC Journal of Library & Information Technology, 2002)
This paper offers relatively unusual form of a report from the Bombay Library network (BONET) Instead of reporting the umber of members, list of lectures given etc. ( some such details are given in Annexure for the readers who are interested in them). This paper presents the essence of lessons learnt by running the BONET over last few years. BONET has been able to contribute to the activities concerned with the absorption of new technology by practitioner in the library and information science. Future plans including electronic publishing are also given. http://dx.doi.org/10.14429/dbit.16.2.3255